2013
DOI: 10.1016/j.bbr.2013.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Short-term memory acquisition in female Huntington's disease mice is vulnerable to acute stress

Abstract: Huntington's disease (HD) is a neurodegenerative disorder marked by cognitive, psychiatric and motor decline, and is modifiable by unidentified environmental factors. We examined the effects of stress on cognitive function in R6/1 HD transgenic mice. Utilizing the Y-maze to assess short-term memory, we report that only female HD mice displayed vulnerability to 1h of confinement stress reflected by impaired memory acquisition. This could not be attributed to a different corticosterone response or exploratory be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Cognitive dysfunction, including impaired short-term memory, is a prominent symptom in HD (Meudell et al, 1978;Scholz and Berlemann, 1987). Short-term memory deficits in the Y-maze test develop at 8 weeks of age in male R6/1 HD mice (Mo et al, 2013) and we now report that 5 days of oral CORT treatment accelerated this deficit in male HD mice. The dose of CORT used in our study was moderate (Karatsoreos et al, 2010) and WT mice were spared from any CORT-induced Y-maze deficits.…”
Section: Corticosterone Treatment Accelerated the Onset Of Y-maze Memsupporting
confidence: 54%
See 2 more Smart Citations
“…Cognitive dysfunction, including impaired short-term memory, is a prominent symptom in HD (Meudell et al, 1978;Scholz and Berlemann, 1987). Short-term memory deficits in the Y-maze test develop at 8 weeks of age in male R6/1 HD mice (Mo et al, 2013) and we now report that 5 days of oral CORT treatment accelerated this deficit in male HD mice. The dose of CORT used in our study was moderate (Karatsoreos et al, 2010) and WT mice were spared from any CORT-induced Y-maze deficits.…”
Section: Corticosterone Treatment Accelerated the Onset Of Y-maze Memsupporting
confidence: 54%
“…We recently reported that male R6/1 mice display a Y-maze deficit from 8 weeks of age (Mo et al, 2013) and female R6/1 mice from 10 weeks of age (unpublished data). We therefore began CORT treatment at 6 weeks of age and tested mice at 7 weeks of age to assess whether the 5-day CORT treatment would accelerate the onset of the Y-maze deficit in HD animals.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Experimental elevation of CORT in the male R6/1 HD mouse exacerbates cognitive symptoms, reduces hippocampal neurogenesis, and slows weight gain (Mo et al , 2014a). Similarly, short-term stress in the R6/1 model exacerbates memory impairment in female HD mice (Mo et al , 2013), while long term stress reduces weight gain in male and female HD mice, reduces saccharine preference in female HD mice (a depressive-like measure of anhedonia), and reduces olfactory sensitivity (Mo et al , 2014b). In the series of experiments presented here, we extend these findings and demonstrate that elevated corticosterone in the R6/2 model dramatically exacerbates the weight loss phenotype in these mice and also shortens lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…Stress paradigms have been shown to exacerbate the phenotype of several mouse and rat models of Parkinson’s [7176], yet there do not appear to be studies attempting to target stress pathways therapeutically within these models. Furthermore, early reports have shown that stress paradigms have a detrimental effect on the phenotype of the R6/1 mouse model of Huntington’s [77, 78]. Further investigation into the mechanisms of how stress signaling affects these proteinopathies is needed, and should also grow to include other neurodegenerative proteinopathies such as Amyotrophic Lateral Sclerosis (ALS) and FTD.…”
Section: Main Textmentioning
confidence: 99%